1983
DOI: 10.1007/bf01906669
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in myocardial contractility in the rat

Abstract: We examined the intrinsic contractile performance of papillary muscles removed from the left ventricle of male and female Wistar rats. Muscles were studied isometrically and isotonically, stimulated at 0.1 Hz, perfused with Tyrode's solution having an external calcium concentration = 2.4 and maintained at 30 ~ In addition, we examined muscle response to changes in external calcium, added norepinephrine or verapamil and alterations in contraction frequency. No significant change in peak isometric development te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 31 publications
7
40
1
Order By: Relevance
“…A number of studies have shown that healthy premeno- pausal women have higher ejection fractions when compared to healthy age-matched men (40,41) or to postmenopausal women (42). Similarly, papillary muscles from female rats have higher rates of shortening than male (43) and than gonadectomized female rats (44). The absence of sex-specific adaptive functional changes in our study suggests that this estrogen effect may be important for baseline cardiovascular characteristics, but not for adaptive functional cardiac changes due to exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that healthy premeno- pausal women have higher ejection fractions when compared to healthy age-matched men (40,41) or to postmenopausal women (42). Similarly, papillary muscles from female rats have higher rates of shortening than male (43) and than gonadectomized female rats (44). The absence of sex-specific adaptive functional changes in our study suggests that this estrogen effect may be important for baseline cardiovascular characteristics, but not for adaptive functional cardiac changes due to exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…Females have greater heart weight per body weight and greater aortic flow than males (Berg & Harmison, 1955;Shreiner, Weisfeldt & Shock, 1969). Moreover, in vitro studies of intrinsic myocardial contractile performance have revealed that females exhibit greater velocity of fiber shortening and shorter time to peak tension than males, even though no sex differences were observed in myocardial elasticity or in the peak tension developed (Capasso, Remily, Smith, & Sonnenblick, 1983). This evidence suggests that sex-related differences in myocardial contractile function may exist.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that there are sex differences in (1) intrinsic contractile properties (Capasso et al, 1983); (2) the positive inotropic response to Ca 2+ o (Wang et al, 1998); (3) Ca 2+ channels in the heart (Ishii et al, 1988) and (4) hormone responsiveness (Capasso et al, 1983;Schwertz et al, 1999). Whether there are sex differences in [Ca 2+ o ] or cardiac sensitivity to Ca 2+ in fishes is not known.…”
Section: +mentioning
confidence: 99%
“…Thus, in contrast to sex steroids, it appears that the positive inotropy observed with Epi and Ca 2+ o in the ventricle of rainbow trout is mediated predominantly through trans-sarcolemmal Ca 2+ influx. (Capasso et al, 1983), including higher sensitivity to Ca 2+ in atria from female rat hearts compared with male hearts (Wang et al, 1998;Schwertz et al, 1999). In addition, Vizgirda et al hypothesized that SR Ca 2+ uptake via Ca…”
Section: Other Inotropes (Epi and Ca 2+ ) Do Not Require Exogenous Glmentioning
confidence: 99%